2020
DOI: 10.3382/ps/pez501
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus and Brassica juncea extruded-expelled cake and solvent-extracted meal as feedstuffs for laying hens: Lay performance, egg quality, and nutrient digestibility

Abstract: Two experiments evaluated feeding Brassica ( B. ) napus (canola) or B. juncea co-products to brown-shelled egg laying hens. In Exp. 1, diets including 20% B. napus or B. juncea extruded-expelled cakes ( NC, JC ) or solvent-extracted meals ( NM, JM ) compared to a control diet with no Brassica co-products, were fed to 120 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
3
1
3
Order By: Relevance
“…Compared to the data reported by Oryschak et al (2020), the results obtained in this study have shown the beneficial effect of using rapeseed meal in combination with flaxseed meal, although the addition level in ratio was lower compared to the tested one in Oryschak et al (2020) study. In a similar study (Yuan et al 2019), the effects of including two different levels of rapeseed oil (2% and 4%) on production performance, egg quality and biochemical parameters of poultry were evaluated.…”
Section: Egg Yolk Fatty Acid Contentcontrasting
confidence: 73%
See 2 more Smart Citations
“…Compared to the data reported by Oryschak et al (2020), the results obtained in this study have shown the beneficial effect of using rapeseed meal in combination with flaxseed meal, although the addition level in ratio was lower compared to the tested one in Oryschak et al (2020) study. In a similar study (Yuan et al 2019), the effects of including two different levels of rapeseed oil (2% and 4%) on production performance, egg quality and biochemical parameters of poultry were evaluated.…”
Section: Egg Yolk Fatty Acid Contentcontrasting
confidence: 73%
“…Regarding the rapeseed meal use, the results obtained by Oryschak et al (2020) showed that including two different varieties of rapeseed, meal or cake (20%) in laying hens' diet indicated a SFA content decrease in the experimental groups compared to the C group (between 27.00% and 27.44%), while the MUFA content increased, although insignificant (P > 0.05) compared to the C group. The PUFA content decreased in all experimental groups compared to the C group, the tendency was observed also in PUFA ω-3 and ω-6 content.…”
Section: Egg Yolk Fatty Acid Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…This might be due to a longer rearing period of laying hens compared to the broilers along with feeding cultivars with varying level of glucosinolate and erucic acid. Previous chicken studies with Brassica products have recommended inclusion levels ranging from 5 to 25%, largely because of variable nutrient profiles and different glucosinolate levels present in different Brassica products ( Oryschak et al., 2020 ). Ashnie et al.…”
Section: Introductionmentioning
confidence: 99%
“…У коричневых кур-несушек при добавлении 30 % рапсового жмыха или шрота к рациону (контроль -без добавок) достоверно (p < 0,01) снижалась масса яиц, переваримость сухого вещества рационов на 5 %, сырого протеина -на 4 %, использование валовой энергии -на 7 %, а также переваримость всех незаменимых аминокислот, за исключением триптофана. Из положительных эффектов отмечено достоверное (р < 0,01) повышение на 1,6 % содержания мононенасыщенных жирных кислот (МНЖК) в желтке (27). То, что перечисленные негативные эффекты связаны именно с антипитательными веществами рапса (ГЛ и эруковой кислотой), подтверждается результатами другого опыта, в котором изучали влияние экспеллерного шрота (7 и 14 % в рационе против 30 % в опыте M.A.…”
unclassified